PERBAIKAN LINGKUNGAN KERJA PADA PENGRAJIN UKIRAN KELONGSONG PELURU DENGAN MENYESUAIKAN TINGGI MEJA KERJA DI DESA KAMASAN, KLUNGKUNG - Soewarno, Aik (Jurnal Natah; Vol. 3, No. 2 Agustus 2005)
Bali is a province located in Indonesia, which is well known as its tourism. Tourism which consists of educational, cultural, social, and economic aspect as well, be able to provide obviously job opportunity in this area. Handicraft of bullet shell in Kamasan Village has a potency to offer the chance of employment which will enhance the community income. To increase their performance, this can be attained both through providing capital additional and increasing the quality of their works. The work behavior which is safe, health and comfortable, will tend to conquer the high productivity in a long period. Ergonomics is a relation between human and their work environment. This means all relations among tools, materials, organization or work method and its environment as well. At Kamasan Village, most carvers have behavior working on sit position. Inappropriate between sit position and level of table lead to create a “force manner”. If this happens on a long term, it will create painful on their part of body. Based on mentioned above, the writer conducted a research regarding working manner of traditional carver which result painful on joint angle. The problem is how to eliminate “force manner” of the carver of bullet shell at Kamasan Village. The purpose of this research is to give an information to the carver of bullet shell to fit their table dimension suitable with the user in order to work healthy, safely, comfortable, efficiently and finally lead to increase their work productivity. Based on anthropometry data which is compared to the theory of working manner, is able to be designed ergonomically the dimension of table and working tools. The research shows that through improving the working manner which is appropriate with the anthropometry of the carver and providing better job training for the workers, will give safety, comfortable and enhance their work productivity.
Keywords: working manner, ergonomics, anthropometry and work productivity.